Procalcitonin as a Tool to Antimicrobial Stewardship in COVID-19 Patients with Superimposed Bacterial Infections: A Systematic Review - Omer I; Abuthiyab N; Al Zaid N; Alkanani R; Abualnaja R; Khan G (Dove Medical Press, 2022)
Ibrahim Omer,1,2 Noorah Abuthiyab,1,2 Nura Al Zaid,1,2 Raghad Alkanani,1,2 Reema Abualnaja,1,2 Ghadeer Khan1,2 1College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 2King Abdullah International Medical Research Center, Jeddah, Saudi ArabiaCorrespondence: Ibrahim Omer, College of Medicine, KSAU-HS, Jeddah, Saudi Arabia, Email Ibraheem.a.omer@gmail.comAbstract: Procalcitonin is an inflammatory marker that had shown marked potential as an antimicrobial stewardship tool for administering antibiotics when needed in patients with pneumonia as it raises concurrently with other inflammatory markers, yet no systematic review has assessed its potential in COVID-19 patients. This systematic review aimed to assess the potential appropriateness of procalcitonin as an antimicrobial stewardship tool in COVID-19 patients with superimposed bacterial and non-bacterial infections. All study designs published after 2019 were included in this systematic review. We included all studies that had reported procalcitonin levels in COVID-19 patients with suspected superimposed secondary infection(s). We searched MEDLINE, Scopus, and the Directory for Open Access Journal from April 2022 to May 2022 and retrieved all related articles for screening with no restrictions on language. We conducted risk of bias assessment according to the Critical Appraisal Skills Programme (CASP) criteria for cohort and case-control studies. Results were presented according to procalcitonin cut-off values, gold standard test used to confirm infection, and overall study conclusion(s), among other variables. This systematic review included 18 articles with 7196 patients in 8 countries. Despite different cut-off values of procalcitonin used, thirteen studies had indicated the appropriateness of using procalcitonin as antimicrobial stewardship tool in COVID-19 patients. We urge physicians to take this into account when treating COVID-19 patients suspected of superimposed infections and we look forward to further studies with standardized procalcitonin cut-off values that may provide appropriate quantitative data that can contribute to clinical guidelines.Registration (PROSPERO): CRD42022315013.Keywords: procalcitonin, COVID-19, bacterial pneumonia, antimicrobial stewardship